PRODUCTION CAPACITY PLANNING BASED ON SALES FORECAST USING CUT AND TRY METHOD - Hernadewita Hernadewita; Hendra Hendra; Dafid Mega Saputra; D Daruki; Singgih Juniawan; Uti Roysen (Jurnal Teknologi, 2023)
Companies based on FMCG (Fast Moving Consumer Goods) need to increase productivity and improve efficiency in order to stay afloat to keep pace with the increasing prices of food raw materials as a result of global security geopolitical conditions and drastic changes in climatic conditions. One of the affected is PT. DUS produces the basic ingredients of fast food. The purpose of this study was to determine the most efficient production planning option in order to reduce the company's costs. The methods used in this research are Exponential Smoothing Method, Linear Programming Method, and Mean Absolute Percent Error (MAPE) Method for Forecasting; The Economic Quantity Order method includes the determination of Safety Stock and Re-Order Point to determine the amount of Inventory, and the Aggregate Planning Cut and Try Method to determine production capacity with minimum costs. The results showed that the production plan with options for constant labor plans, constant inventory, and overtime resulted in a cost of Rp. 549,840,000.00 while the constant labor plan options, variations in inventory, and running out of inventory result in a cost of Rp. 1,548,350,000.00.